Farmakoedukasi Literasi Kesehatan Mental dan NAPZA untuk Siswa SMA/SMK - Aminah Dalimunthe; Khairunnisa Khairunnisa; Lisda Rimayani Nasution; Chemayanti Surbakti (Universitas Muhammadiyah Semarang, 2025)
Global data shows that one in seven children aged 10-19 experiences mental health disorders. In Indonesia, one in three adolescents (34.9%), equivalent to 15.5 million Indonesian adolescents, experiences at least one mental health issue per year. Mental health disorders are often associated with the use of NAPZA (Narcotics, Psychotropics, and Addictive Substances). This activity aims to enhance the knowledge and awareness of 9th state vocational high school students about mental health and NAPZA. The community service activities involve socialization and education on mental health and NAPZA abuse, training using Positive bottle and an unspoken word book, and training with